1977
DOI: 10.1093/nar/4.8.2573
|View full text |Cite
|
Sign up to set email alerts
|

Structure of poly 8-bromoadenylic acid: conformational studies by CPF energy calculations

Abstract: Poly 8-bromoadenylic acid [poly(BBrA)] is the only known all-syn polynucleotide. It shows a helix-coil transition with a melting curve centred around 55 degrees C. Energy calculations based on classical potential functions have been used to explore the three-dimensional structure of this polymer in helix and random coil. It is concluded that the ordered state is a helix of two parallel strands with a two-fold rotation axis, and the duplex is stabilised by hydrogen bonds involving N1 and H6. Each strand has a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

1979
1979
2009
2009

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
1
13
1
Order By: Relevance
“…In addition, the readers' attention is drawn to a few recent publications selected out of a vast literature concerning theoretical investigations on polynucleotide conformation (794)(795)(796)(797)(798)(799)(800)(801)(802)(803)(804)(805)(806)(807)(808), the flexibility ofthe double helix (809)(810)(811)(812)(813)(814)(815)(816)(817), and spectroscopic investigations of polynucleotide structures (818)(819)(820)(821)(822)(823)(824). The biochemical structure-function correlations are treated in reviews for DNA (792) and for RNA (793).…”
Section: Polymorphism Of Dna Versus Structural Conservatism Of Rna: Cmentioning
confidence: 99%
“…In addition, the readers' attention is drawn to a few recent publications selected out of a vast literature concerning theoretical investigations on polynucleotide conformation (794)(795)(796)(797)(798)(799)(800)(801)(802)(803)(804)(805)(806)(807)(808), the flexibility ofthe double helix (809)(810)(811)(812)(813)(814)(815)(816)(817), and spectroscopic investigations of polynucleotide structures (818)(819)(820)(821)(822)(823)(824). The biochemical structure-function correlations are treated in reviews for DNA (792) and for RNA (793).…”
Section: Polymorphism Of Dna Versus Structural Conservatism Of Rna: Cmentioning
confidence: 99%
“…Recently studies using multidimensional function minimization procedure were made on the nucleic acid systems (Broyde et al, 1975;1978;Broyde and Hingerty, 1979;Fujii and Tomita, 1976;Kister and Dashevsky, 1976;Govil et al, 1977;Thiyagarajan and Ponnuswamy, 1978a, 1978bZhurkin et al, 1978;Levitt, 1978). These studies brought out many interesting aspects of the influence of the bases in the dimer, their actual sequence on the preferred backbone conformations and base stacking properties.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier investigation (28) of the energetic relationship between a and y in DNA produced maps which predicted the linear correlation between these angles, but picked a::::: 180° to be most stable and did not indicate the minimum at(a=60o, y= 180°). A semi-linear correlation between a andy has also been predicted in maps calculated using only base stacking as a measure of the relative favorablenesses of various conformations (30), supporting the hypothesis that this correlation is an example of the crankshaft effect ~-a Undoubtedly, the most widely studied nucleic acid torsion angle dependence is that between the two P-0 backbone torsions~ (C3'-03'-P-05') and a (03'-P-05'-C5') (15,16,18,20,(22)(23)(24)(25)(26)(27)(28)(29)(34)(35)(36)(37)(38)(39)(40).Thisisaconsequenceofthebeliefthatmuchoftheconformational flexibility of nucleic acids stems from variation in this pair of angles (62,(70)(71)(72). The maps produced in this study are shown in Figure 2h.…”
Section: ~-Ementioning
confidence: 68%
“…Both classical (12,13,15,16,(18)(19)(20)22,(24)(25)(26)(27)(28)(29) and quantum mechanical (34)(35)(36)(37)(38)(39)(40) techniques have been used to evaluate the conformational energies. Oligonucleotide maps fora-y (28) and y-x (17 ,19) have also been reported, but for a large majority of the possible pairs (15 out of 21), including several of particular interest, no maps have heretofore been published.…”
Section: The Energy Contour Maps: Comparison With Previous Calculationsmentioning
confidence: 99%